Pharmacodynamic comparison of esmolol, labetalol, and lignocaine in modulating sympathetic stress response during intubation: A randomized controlled trial. (Student's Journal of Health Research Africa, 2025)
Background:Laryngoscopy and tracheal intubation trigger a pronounced sympathetic stress response, resulting in tachycardia, hypertension, and increased myocardial oxygen demand. Pharmacological attenuation of this response is essential, particularly in patients at cardiovascular risk. Esmolol, labetalol, and lignocaine are frequently used agents, but direct comparative pharmacodynamic data under identical clinical conditions remain limited. Aim:To compare the pharmacodynamic efficacy of esmolol, labetalol, and lignocaine in modulating haemodynamic responses to laryngoscopy and intubation. Methods:This prospective, randomized, double-blind study included 75 ASA I–II patients aged 20–60 years undergoing elective surgery under general anaesthesia. Patients were allocated to receive Esmolol 0.5 mg/kg (Group ES), Labetalol 0.25 mg/kg (Group LB), or Lignocaine 1 mg/kg (Group LG) intravenously 2 minutes before intubation. Heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), and rate-pressure product (RPP) were recorded at baseline, pre-intubation, at intubation, and 1–10 minutes post-intubation. Results:Labetalol produced the most effective attenuation of HR, SBP, DBP, and MAP at intubation and during the first 10 minutes post-intubation (p < 0.05). Esmolol showed moderate suppression, mainly of HR, while lignocaine demonstrated the least haemodynamic control. RPP peaked highest in the lignocaine group (22,030.96), followed by esmolol (15,332.16), and was lowest with labetalol (13,635.60), indicating superior myocardial protection with labetalol. Conclusion:Labetalol is the most effective agent in suppressing the sympathetic haemodynamic response to intubation, followed by esmolol. Lignocaine alone provides inadequate attenuation. RecommendationBased on the findings, labetalol may be preferred as the first-line agent for attenuating haemodynamic stress response during laryngoscopy and intubation, especially in patients at cardiovascular risk.
Keywords: Esmolol; Labetalol; Lignocaine; Intubation stress response; Haemodynamics; Sympathetic attenuation